Infusion of anti-DFS70 antibodies prolonged survival of lupus-prone mice. (February 2021) - Aljadeff, Gali; Shemer, Asaf; Katz, Itai; Andrade, Luis Eduardo C; Gilburd, Boris; Halpert, Gilad; Mahler, Michael; Blank, Miri; Amital, Howard; Shoenfeld, Yehuda
Background: Systemic-lupus-nephritis is a chronic autoimmune disease characterized by immune complex deposition and a flare of autoantibodies and leading to renal injury. Objectives: To expose anti-Dense-Fine-Speckled-70 (DFS70)-antibodies to genetically-prone-lupus-mice. Methods: NZBXW/F1 female mice were monitored for the onset of glomerulonephritis by proteinuria upon infusion of anti-DFS70 (40 μg/mouse), commercial-human-IgG (cIgG) or phosphate-buffered-saline (PBS) as controls. The survival time was detected by mice death. Circulating anti-dsDNA were tested by ELISA. Proteinuria, was defined by a standard semi-quantitative-Bayer-Multistix-dipstick. Kidney histology was analyzed by periodic-acid–Schiff-PAS staining. Results: A significantly higher percentage of anti-DFS70-infused mice exhibited prolonged survival time as compared with cIgG and PBS-subjected mice (p < 0.022). One mouse out of 10 mice injected with anti-DFS70-antibodies died at week 36, whereas, 6 out of 10 mice subjected with PBS found dead at this time. Eighty percent of anti-DFS70 injected mice did not show severe glomerulonephritis by histology. Conclusions: anti-DFS70 attenuated the progression of glomerulonephritis and prolonged the survival time. Circulating anti-DFS70-autoantibodies may confer a protective role against renal injury in murine-lupus-nephritis. Our data may propose a novel therapy approach for lupus patients.